Layanan Konsultasi Bimbingan dan Konseling pada Madrasah Tsanawiyah Negeri Sekota Banjarmasin - Fadillah, Haris (Tarbiyah, 2014)
Based on the research, the implementation of consulting services at State Islamic Junior High Schools (MTs Negeri) in Banjarmasin is equated with individual counseling. Counseling teacher invites teachers parents to come to the schools to consult anything with regards with rules violations and problems that students do in the schools. The implementation of consulting services are given through a way of bringing all the parties in a room that should be discussed in individual counseling services, but they are then discussed in consulting services and the issue thashould be discussed is the existing third-partyâs problem which has direct connection with consultee. The research also found out, that there is a gap between theory and practice. There are some indications that the guidance and counseler teachers at State Islamic Junior High Schools (MTs Negeri) in Banjarmasin have a misperception about implementation consulting services, consulting services performed for changing the meaning into individual counseling so that the operationalization of the consulting services is less well targeted.